Linguistic landscape and visitors’ perception of written information at museums in Bali - Susianti, Hartanti Woro; Ni Kade Juli Rastitiati; I Gusti Ngurah Agung Suprastayasa (Englisia Journal, 2025)
This study examines the linguistic landscape (LL) of several museums in Bali, with a particular focus on language contestation, underlying linguistic ideologies, and visitor perceptions. It explores how written information is presented, the languages prioritized, and how these linguistic choices reflect identity construction and social functions within museum spaces. The research employs a qualitative design, incorporating photographic documentation, direct observation, and visitor interviews conducted across multiple museums. The findings indicate that multilingual signage is a defining feature of these museums, most commonly combining Indonesian with English or other foreign languages such as Japanese, German, and Dutch. Balinese script is also present, though often used to convey information in Indonesian rather than in the Balinese language. The instrumental function of LL is reflected in the strategic use of foreign languages to accommodate international visitors, while its symbolic or indexical function emerges in the use of Indonesian and Balinese script as markers of national and local identity. Visitor feedback suggests that while much of the written information is clear and useful, issues remain regarding font size, aesthetics, and accessibility. Overall, the study highlights how LL in Bali’s museums embodies both communication practices and broader cultural, ideological, and institutional dynamics.